Evaluation of Exposure to Impulse Noise at Personnel Occupied Areas During Military Field Exercises - MŁYŃSKI, Rafał; KOZŁOWSKI, Emil; USOWSKI, Jacek; JURKIEWICZ, Dariusz (Archives of Acoustics, 2018)
The tests reported in this paper were carried out to evaluate the exposure of soldiers to noise at operator and control positions during military field exercises. The tests were conducted during firing from a T-72 tank, a BWP-1 Infantry Fighting Vehicle, antitank guided missiles, a ZU-23-2K anti-aircraft gun, and a 2S1 GOZDZIK howitzer. The evaluation of noise exposure showed that the limit values of sound pressure level, referred to by both Polish occupational noise protection standards and the Pfander and Dancer hearing damage risk criteria developed for military applications, were repeatedly exceeded at the tested positions. Despite of the use of tank crew headgear, the exposure limit values of sound pressure level were exceeded for the crew members of the T-72 tank, the BWP-1 infantry fighting vehicle, and the 2S1 GOZDZIK howitzer. The results show that exposure of soldiers to noise during military field exercises is a potentially high hearing risk factor.